2022
DOI: 10.1021/jacs.1c10450
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Twisting of C-Centered Octahedral Gold(I) Clusters by Chiral N-Heterocyclic Carbene Ligation

Abstract: Asymmetric induction of metal clusters by ligation of chiral ligands is intriguing in terms of the mechanism of chirality transfer and the stability of the resulting chiral structure. Here we report the asymmetric induction of C-centered hexagold(I) CAu I 6 clusters into an asymmetrically twisted structure through monodentate, chiral benzimidazolylidene-based N-heterocyclic carbene (NHC) ligands. X-ray diffraction analysis revealed that the NHC-ligated CAu I 6 cluster was diastereoselectively twisted with dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 49 publications
(78 reference statements)
0
40
0
Order By: Relevance
“…SCXRD analysis demonstrates that R / S -Ag 12 Ag 32 and R / S -Au 12 Ag 32 crystallize in the chiral cubic space group P 432 (Tables S2 and S3), which is rarely observed among crystallized chiral clusters. S -type S -Ag 12 Ag 32 and S -Au 12 Ag 32 as representatives are described in the following structural analysis. The inorganic framework of the S -Ag 12 Ag 32 cluster can be described as a concentric three-layer core-shell structure S 2– @Ag 12 @S 8 @Ag 32 with S 2– as the anion template, similar to a Russian nesting doll (Figure a).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…SCXRD analysis demonstrates that R / S -Ag 12 Ag 32 and R / S -Au 12 Ag 32 crystallize in the chiral cubic space group P 432 (Tables S2 and S3), which is rarely observed among crystallized chiral clusters. S -type S -Ag 12 Ag 32 and S -Au 12 Ag 32 as representatives are described in the following structural analysis. The inorganic framework of the S -Ag 12 Ag 32 cluster can be described as a concentric three-layer core-shell structure S 2– @Ag 12 @S 8 @Ag 32 with S 2– as the anion template, similar to a Russian nesting doll (Figure a).…”
Section: Resultsmentioning
confidence: 97%
“…So far, the enantiopure clusters all protected by homochiral thiolate ligands have been scarce. At present, chiral P-based, CC-based, and NHC-stabilized ligands have been successfully used for preparing enantiopure metal clusters characterized by SCXRD. However, because of the difficulty in synthesis, there are few chiral sulfur-based ligands for the synthesis of atomically precise metal clusters, although chiral sulfur ligands (GSH) are first used to prepare gold clusters …”
Section: Introductionmentioning
confidence: 99%
“…The XRD peaks at 2θ= 12.18, 12.84, 14.61 and 45.64 o can be observed in Figure 8b. This can also be due to the structured formation of NHCs [49].…”
Section: Tga and Xrd Analysismentioning
confidence: 99%
“…It turns out that, within the framework of our general investigations on the stabilization of AuNCs by N-heterocyclic carbenes (NHCs), we found that some NHCs can, in certain circumstances, stabilize cuboctahedral cluster cores, suggesting rational control of the core structure with respect to the nature of the ligand shell. NHCs have been recently introduced in AuNC chemistry as alternative neutral two-electron ligands of phosphines and appear to favor promising photoemissive properties. This is why we recently investigated, by means of density functional theory (DFT) calculations (see the Supporting Information for Computational Details), hypothetical NHC analogues of the eight-electron phosphine/halogenide heteroleptic clusters [Au 13 (PR 3 ) n X 12– n ] ( n −7)+ (X = halogen). , Interestingly, our calculations show that, at least in the tetrabromide case, the cuboctahedral [Au 13 (NHC) 8 Br 4 ] + species can be stabilized, as described below.…”
mentioning
confidence: 95%
“…Finally, because of the relevant photoluminescent properties reported for the experimentally characterized NHC-protected AuNC series ascribed to a phosphorescent emission originating from the T 1 → S 0 decay, it is also interesting to see the difference in the phosphorescent emissions induced by core isomerization in the investigated [Au 13 ( i PrIm) 8 Br 4 ] + isomers. As for most of the known eight-electron superatoms , the T 1 states of both isomers can be viewed as the result of a HOMO (1P) → LUMO (1D) excitation (Figures S5 and S6).…”
mentioning
confidence: 98%